Hungarian Monitoring, 2 January 1990 . [Magyar rádiófigyelő], 1990. január 2 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Calm slowly returns to Romania - Havel's introductory visit to Munnich - Serious national skirmishes in the Karabakh region and at the USSR-Iran border Domestic Affairs: - Judit Csehák's briefing on medical aid sent to Romania - Mátyás Szűrös at Hajdú-Bihar County council meeting - Election campaign begins - Census begins - Hungarian Helsinki Committee in support of equality for minorities in Romania Economy: - Entrepreneurs hold protest against State Tax Authority - Pét Nitrogen Works seeks new director again - On the conditions to make the Forint convertible Külpolitika: - Romániában helyreáll lassan a nyugalom - Havel bemutatkozó látogatása Münchenben - Súlyos nemzetiségi összetűzések voltak Karabah hegyvidéken és a szovjet-iráni határnál Belpolitika: - Csehák Judit tájékoztatója a Romániába küldött gyógyászati segédeszközökről - Szűrös Mátyás a Hajdú-Bihar megyei Tanács ülésén - Beindult a választási kampány - Megkezdődött a népszámlálás - A Magyar Helsinki Bizottság a romániai kisebbségek egyenjogúságáért Gazdaság: - APEH-ellenes tüntetést tartottak a vállalkozók - A Péti Nitrogénművek ismét gazdára vár - A forint konvertibilissé tételéről